Dropping out of learners with hearing impairment from inclusive classes in urban schools in Bulawayo - Loveness Dube (International Journal of Studies in Inclusive Education)
This study explored factors contributing to the dropping out of learners with a hearing impairment from inclusive classes. It used the interpretivism theory to extract rich data and the qualitative research approach to conduct the study. A case study was used as a research design. In this study, participants were purposively selected. Semi-structured interviews, observations, and document analysis were used to collect data. The findings from the study revealed the challenges encountered in the teaching and learning of learners with hearing impairment. These include curriculum adaptation, social interaction with peers, negative attitudes of teachers and hearing learners, parental involvement, communication barriers, lack of interpreters, high learner ratio, and lack of resources. The findings further revealed that some opportunities are being gained by learners with hearing impairment in inclusive classes, such as access to a wider curriculum, social interaction, enhanced communication, and learning in local schools. However, challenges seemed to outweigh the opportunities gained by learners with hearing impairment, compelling them to drop out of inclusive classes. Therefore, the study gave some recommendations to help curb the dropping out of learners with hearing impairment from inclusive classes. These include allocating more resources in inclusive classes to address the problem of inadequate materials and the fact that government policies on inclusion should be made available to all educators and fully implemented. In addition, supervision, monitoring, support from parents, and evaluation of the system should be done to facilitate the learning of learners with hearing impairment in inclusive classes.